Direct calculations of the CH4+CO2 far infrared collision-induced absorption. (June 2022) - Fakhardji, Wissam; Boulet, Christian; Tran, Ha; Hartmann, Jean-Michel
Highlights: Direct calculations using an anisotropic intermolecular potential Good agreement with measurements without using any adjusted parameter Demonstration of the limits of the isotropic approximation Predictions of the influence of temperature for planetary studies Abstract: We present computations, solely using input data from the literature and thus free of any adjusted parameter, of the far infrared collision-induced absorption (CIA) by interacting CH4 and CO2 molecules. They are based on classical molecular dynamics simulations (CMDS) of the rotational and translational motions of the molecules made using an accurate ab initio CH4 -CO2 anisotropic intermolecular potential, and on a long-range expansion of the interaction-induced dipole. Various desymmetrization procedures, which all ensure detailed balance of the spectral density function are a posteriori applied to the CMDS results. The comparison with the available measurements, which have been collected at room temperature, shows that a good agreement can be obtained without introducing any ad hoc short-range dipole components, and it enables to point out the limits of some of the desymmetrization procedures. Tests are also made of the so-called "isotropic approximation", which point out its strong limits, since it leads to large underestimations of the CIA, and question previous computations made using an isotropic potential and long-range expansion of the induced dipole complemented by ad hoc contributions at short distances. Finally, the temperature dependence of the CIA is predicted for applications to planetary atmospheres.